Why do we love zombie movies? An examination of the grotesque images of a mass culture product, as compared to postmodern consummerist culture (Palíndromo, 2015)
This article seeks to analyze com- mercial horror movies, specifically those themed on zombies and the undead, proposing approximations between the images produced by filmmakers and art- ists and the consumer culture produced under capitalism. If the filmmaker, as proposed by Jameson (1995), is not iso- lated from its social and political con- text, could these films be understood as possible images of what Lukács (1920) understands as the bankruptcy of cap- italist social organization? In a culture where death, exhaustion of resources, chaos and decay of organizations are recurring situations, how could these commonplace themed films be reinter- preted as image of capitalism itself?
Keywords: film analysis; post-modern culture; capitalist culture; consumerism; zombies movie